Exploring Employer Branding and Internal Marketing in Specific Tourism Contexts: Preliminary Approach - Bruno Barbosa SOUSA; Francisco Barbosa GONÇALVES (Communications of International Proceedings, 2024)
Human capital is a competitive factor that allows to obtain a greater competitive advantage over competitors, so there is a growing concern on the part of companies to keep their employees engaged with their mission, vision and values. Organizations need people, their technical and human potential. Employer branding is based on a commitment between the organisation and the employee, which has raised the interest of many experts in the marketing sector, since this relationship portrays a promise of mutual investment and trust. Currently, the tourism and hospitality sector faces global challenges in attracting and retaining talent for several reasons, such as unskilled labour, high turnover rate, excessive working hours, high competition and low pay. This study aims to explore internal marketing and employer branding applied in the tourism sector, which is intended to correlate these very current and little-explored themes. From an interdisciplinary perspective, the manuscript presents some preliminar insights for tourism (internal perspective) and for marketing strategies in specific tourism contexts. At the end, final considerations and future paths are discussed.
Keywords: Employer Branding; Internal Marketing; Retention; Talent Attraction; Tourism